2013
DOI: 10.2527/jas.2012-5799
|View full text |Cite
|
Sign up to set email alerts
|

Meat Science And Muscle Biology Symposium: Developmental programming in cattle: Consequences for growth, efficiency, carcass, muscle, and beef quality characteristics1,2

Abstract: This paper reviews results of studies on effects of fetal programming and maternal nutrition during pregnancy on growth, efficiency, carcass, muscle, and meat quality characteristics of cattle. It includes results from our Australian Beef Cooperative Research Centre studies on factors such as chronic severe nutritional restriction from approximately d 80 of pregnancy to parturition and/or throughout lactation used to create early-life growth differences in the offspring of cows within pasture-based systems and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 59 publications
1
59
1
1
Order By: Relevance
“…These findings are at odds with the suggestion, based largely on more mechanistic evidence within fetal life and in species other than cattle, that nutrition during gestation may alter fatness and marbling at market weights (Du et al, 2013). In contrast, better maternal nutrition from birth to weaning within pasture-based systems resulted in more rapid growth of offspring and a small but persistent increase in carcass fatness, but not in marbling (Greenwood et al, 2006Robinson et al, 2013), consistent with lack of effect of initial BW (which is indicative of growth and nutrition to weaning) on marbling score or on IMF content of the 5 muscles in the present study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These findings are at odds with the suggestion, based largely on more mechanistic evidence within fetal life and in species other than cattle, that nutrition during gestation may alter fatness and marbling at market weights (Du et al, 2013). In contrast, better maternal nutrition from birth to weaning within pasture-based systems resulted in more rapid growth of offspring and a small but persistent increase in carcass fatness, but not in marbling (Greenwood et al, 2006Robinson et al, 2013), consistent with lack of effect of initial BW (which is indicative of growth and nutrition to weaning) on marbling score or on IMF content of the 5 muscles in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…The stages of development at which the amount of marbling at market weights can be influenced by nutrition, either by earlier effects on adipogenesis and/or by the persistence of effects on lipogenesis, has been the subject of numerous studies. Within pasture-based nutritional systems similar to the present study, neither birth weight or varying maternal nutrition at pasture during pregnancy affected rib fat depth, P8 rump fat depths, MSA marbling score, or LM IMF content in Bos taurus cattle at heavy market weights (380 kg average carcass weight; Greenwood et al, 2006;Greenwood and Cafe, 2007;Robinson et al, 2013). These findings are at odds with the suggestion, based largely on more mechanistic evidence within fetal life and in species other than cattle, that nutrition during gestation may alter fatness and marbling at market weights (Du et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Effects specific to maternal nutrition during pregnancy are difficult to detect because they may affect the postnatal nutritional status of the dam and nutrition of the offspring as well. However, studies performed on cattle, as part of the Australian Beef Cooperative Research Centre, used a factorial experimental design to separate pregnancy-and lactation-specific effects (see Robinson et al 2013). Importantly, the findings suggest that the effects of maternal nutrition during pregnancy and lactation are additive and a lifetime approach should be taken rather than simply investigating the effects at a particular stage of development (Robinson et al 2013).…”
Section: Muscle Fibre Numbermentioning
confidence: 99%
“…Therefore, it can be concluded that discrepancies among studies in the literature may be attributed not only to different levels of feed restriction, different environmental conditions, number of parturition or genotype, but to the different daily feed intake of the control groups as well. The negative effect of feed deficit during pregnancy on offspring's birth weight is also well documented in other farm animals (Wu et al, 2006) such as cattle (Robinson et al, 2013), pigs (Bee, 2004, sheep during late pregnancy (Reed et al, 2007;Swanson et al, 2008), but not in sheep during mid pregnancy (Daniel et al, 2007).…”
Section: Resultsmentioning
confidence: 91%
“…With regard to farm animals, the effects of maternal undernutrition during gestation on performance and/or body composition of the offsprings has been extensively studied in sheep (Krausgrill et al, 1999;Fahey et al, 2005;Zhu et al, 2006;Daniel et al, 2007), pigs (Bee, 2004;Gondret et al, 2005;Rehfeldt and Kuhn, 2006) and cattle (Long et al, 2010;Robinson et al, 2013). In rabbits, feed restriction in late pregnancy may alter mortality rate and birth-to-weaning weights (Nafeaa et al, 2011), although the timing of feed restriction is likely important for reproductive performance (Manal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%